Frequency-domain multiuser detection for CDMA systems - Silva, Paulo (River Publishers series in communications., 2012)
In Frequency-Domain Multiuser Detection for CDMA Systems the use of PA block transmission is considered in the context of both DS (Direct Sequence) and MC (Multicarrier) CDMA schemes.